Annual review of comparative and international education 2022 - Wiseman, Alexander W. (Emerald Publishing Limited, 2023)
Since 2013, the Annual Review of Comparative and International Education has covered significant developments in the intersecting fields of comparative education, international education, and comparative and international education. Reflecting on ten prolific years of publication, both volumes of the 2022 Annual Review together present discussions on education trends and directions, conceptual and methodological developments, research-to-practice, area studies and regional developments, and diversification of the field of education. Featuring authors from around the world, they tell the story of comparative and international education as an academic and professional field and address both the functions and ethics of education across vastly different cultures, communities, organizations, and outcomes. Part B explores research-to-practice, area studies and regional development, and diversification of the field. The Annual Review of Comparative and International Education serves as an important reference, a source of knowledge, a record of the skills and how they are implemented, and a figurative mirror helping scholars and professionals alike reflect on their own practice and what it means both to the field and to each other.
Includes index.
Keywords: Comparative education -- Periodicals.; International education -- Periodicals.; Education -- Comparative.; Multicultural education.; elektronické knihy; electronic books